2020
DOI: 10.1371/journal.pone.0229776
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A in Metabolic syndrome: A systematic review and meta-analysis

Abstract: Objective Fetuin-A has been associated with the progression of metabolic syndrome, but previous studies found inconsistent results on the relationship between metabolic syndrome and the concentration of fetuin-A. The aim of this study was to perform a meta-analysis to summarize previous findings on this relationship. Method This study was registered with the International Prospective Register of Systematic Reviews PROSPERO (CRD42019129566). Studies examining the relationship between metabolic syndrome and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Noteworthy, different chemokine assessment methods were used for different studies. Therefore, to be conservative, the random-effects model was used to determine the standardized mean difference (SMD) and 95% confidence interval (CI) for continuous data (19). Using the restricted maximum-likelihood estimator, the SMD was calculated using the Cohen's d method to synthesize the effect size across studies (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, different chemokine assessment methods were used for different studies. Therefore, to be conservative, the random-effects model was used to determine the standardized mean difference (SMD) and 95% confidence interval (CI) for continuous data (19). Using the restricted maximum-likelihood estimator, the SMD was calculated using the Cohen's d method to synthesize the effect size across studies (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the cystatin superfamily and is produced majorly by hepatic and adipose tissues. Fetuin A has been recognized as a multifunctional molecule related to its role in metabolic processes, insulin resistance, regulation of adipogenesis and mineralization throughout the body [41]. FA is down-regulated by inflammatory mediators and is a negative acute phase protein [42].…”
Section: Fetuin A: Alpha-2-heremans Schmid Glycoproteinmentioning
confidence: 99%
“…Predominantly synthesized and secreted from the liver, fetuin-A is a multi-faceted protein that is an endogenous inhibitor of the insulin receptor tyrosine kinase in the liver, adipose tissue, and skeletal muscle [ 12 , [109] , [110] , [111] , [112] , [113] , [114] ] ( Figure 3 ). Patients with insulin resistance, obesity, and NAFLD have high circulating fetuin-A levels, making it a potential marker of disease prediction and diagnosis [ 12 , [115] , [116] , [117] , [118] ] ( Table 1 ). Purified rat fetuin-A dose-dependently inhibits insulin receptor tyrosine kinase activity, altering insulin signaling and ultimately resulting in insulin resistance [ 109 ] ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fetuin-A is a negative regulator of the adipokine adiponectin and organokines work in concert to regulate insulin resistance ( Figure 3 ) [ 121 , 124 , 125 ]. Conversely, adiponectin has been shown to inhibit fetuin-A expression through the AMPK pathway, and it was recently suggested that hypoadiponectinemia in patients with metabolic syndrome may result in increased circulating fetuin-A [ 118 ]. In patients with type 2 diabetes, 12 weeks of calorie restriction significantly decreased circulating fetuin-A concentrations, resulting in improved visceral fat, plasma glucose, blood pressure, and lipid profiles [ 126 ].…”
Section: Introductionmentioning
confidence: 99%